Analysis of the Effects of Ex–Ante Risk Management Strategies on Agripreneurs Financial Performance in North Central Nigeria (International Journal of Scientific Research and Management (IJSRM), 2021)
This study evaluated the effect of ex-ante risk management strategies on agripreneur’s financial performance in North Central Nigeria. The multistage random sampling technique was adopted in the selection of the agripreneurs that was used to select 300 respondents from Nasarawa, Niger and Kogi States .Well -structured questionnaires were used to elicit the required data from the respondents. Descriptive statistics and multiple regression analysis were used to analyze the data. The agripreneurs adopted risk identification, risk evaluation and risk communication as ex-ante risk management strategies. Brainstorming was used by 33.33 percent of the agripreneurs, which is the major type of risk identification technique adopted. The failure mode and effect analysis method of risk evaluation was adopted by majority of the agripreneurs representing 38.67 percent of the respondents. 28.30 percent of the agripreneurs communicated issues relating to risk from the management to the worker. The value of the R2 for the input, production, processing, marketing and service models indicate that 82.1%, 87.2%, 78.4%, 90.9% and 76.9% of the total variations in the dependent variable were due to the variability of the independent variables. This implies that the ex-ante risk management strategies adopted by the agripreneurs have significant effect on their financial performance. Agripreneurs should be enlightened that risk is essential in the success of a business as entrepreneurs with high risk attitude may earn more returns. Government should come up with policies meant to protect agripreneurs from undue risk exposure to reduce the level of risk.